2004
DOI: 10.1152/ajpendo.00197.2004
|View full text |Cite
|
Sign up to set email alerts
|

Neural regulation of glucagon-like peptide-1 secretion in pigs

Abstract: like peptide (GLP)-1 is secreted rapidly from the intestine postprandially. We therefore investigated its possible neural regulation. With the use of isolated perfused porcine ileum, GLP-1 secretion was measured in response to electrical stimulation of the mixed, perivascular nerve supply and infusions of neuroactive agents alone and in combination with different blocking agents. Electrical nerve stimulation inhibited GLP-1 secretion, an effect abolished by phentolamine. Norepinephrine inhibited secretion, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 48 publications
5
59
1
7
Order By: Relevance
“…In fact, in a recent study where glucose levels were clamped at a permissive level (6 mmol/L [108 mg/dL]), an insulin response could not be demonstrated, whereas the secretion of pancreatic polypeptide (known to strongly depend on vagal efferent activity [12]) was greatly increased (13). Similarly, demonstrating any clear cephalic phase for the secretion of gut hormones involved in the incretin effect has been difficult (13), and although it is easy to demonstrate experimentally an effect of the efferent vagus nerves on the secretion of gastric and pancreatic hormones (14) (but not gut hormones [15]), this mechanism is not clearly activated in the initial response to meals.…”
Section: Anticipatory Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in a recent study where glucose levels were clamped at a permissive level (6 mmol/L [108 mg/dL]), an insulin response could not be demonstrated, whereas the secretion of pancreatic polypeptide (known to strongly depend on vagal efferent activity [12]) was greatly increased (13). Similarly, demonstrating any clear cephalic phase for the secretion of gut hormones involved in the incretin effect has been difficult (13), and although it is easy to demonstrate experimentally an effect of the efferent vagus nerves on the secretion of gastric and pancreatic hormones (14) (but not gut hormones [15]), this mechanism is not clearly activated in the initial response to meals.…”
Section: Anticipatory Eventsmentioning
confidence: 99%
“…Of note, GPR40-dependent fatty acid detection by L cells also seems to depend on the rate of nutrient absorption, as intestinal perfusion experiments have indicated that the receptor is accessible from the basolateral rather than luminal direction (67). Although close apposition of enteroendocrine cells with the terminals of enteric neurons has been described, the physiological role of neuronal signals in regulating gut hormone secretion remains uncertain (15). Expression of sweet taste receptors on gut endocrine cells, in particular L cells, has been reported as well as activation of these associated with increased secretion (68).…”
Section: Gut Endocrine Regulation Of Glucose Metabolismmentioning
confidence: 99%
“…For both assays sensitivity was below 1 pmol/l, intrassay coefficient of variation below 6 % at 20 pmol/l, and recovery of standard, added to plasma before extraction, about 100 % when corrected for losses inherent in the plasma extraction procedure. Plasma GLP-1 and GIP concentrations were determined as previously described (Hansen et al, 2004). Intestinal content of incretins was determined by radioimmunoassay after extraction of intestinal biopsies (duodenum for GIP assay and ileon and colon for GLP-1 assay) by the method for small samples as described (Holst, Bersani, 1991).…”
Section: Hormonal Determinationsmentioning
confidence: 99%
“…This mechanism seems to be similar to the one described for the insulin secreting β-cell. Furthermore, an important regulator of both β-cells and L intestinal cells is the ANS (Hansen et al, 2004;Rocca, Brubaker, 1999). We have previously shown that the glucose transporter GLUT2 and the GLP-1 receptor are key mechanisms required for glucose-dependent insulin secretion (Guillam et al, 1997;Thorens and Waeber, 1993) and for function of the hepatoportal vein glucose sensor (Burcelin et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…The impaired GLP-1 response may contribute to the impaired regulation of glucagon secretion observed in patients with AN. Possibly an impaired function of the autonomic nervous system may result in impaired GLP-1 secretion, perhaps by influencing gastrointestinal motility [50][51][52]. However, our data show that the total GLP-1 concentration was not dramatically affected by the AN, most likely ruling out impaired neural regulation of GLP-1 secretion.…”
Section: Neuropathy Hampersmentioning
confidence: 53%